Successful surgical treatment of a long ingrowing intra-coronary septic vegetation. (21st May 2021) - Umeda, Yukio
Abstract: A 39-year-old man was referred to our hospital as infective endocarditis with multiple organ failure and disseminated intravascular coagulation syndrome. Transoesophageal echocardiography and coronary computed tomography angiography revealed a long ingrowing vegetation into the right coronary artery. Emergency surgical resection of the vegetation and aortic valve replacement was performed successfully without distal embolism of the vegetation.